An efficient bifunctional electrocatalyst based on a nickel iron layered double hydroxide functionalized Co3O4 core shell structure in alkaline media. Issue 11 (9th May 2019) - Tahira, Aneela; Ibupoto, Zafar Hussain; Vagin, Mikhail; Aftab, Umair; Abro, Muhammad Ishaq; Willander, Magnus; Nur, Omer
Abstract : An electrocatalyst based on a nickel iron layered double hydroxide functionalized Co3 O4 core shell structure. Abstract : Developing highly active nonprecious metal and binder free bifunctional electrocatalysts for water splitting is a challenging task. In this study, we used a simple strategy to deposit a nickel iron layered double hydroxide (NiFeLDH) onto cobalt oxide (Co3 O4 ) nanowires. The cobalt oxide nanowires are covered with thin nanosheets of NiFeLDH forming a core shell structure. The Co3 O4 nanowires contain the mixed oxidation states of Co 2+ and Co 3+, and the surface modification of Co3 O4 nanowires has shown synergetic effects due to there being more oxygen defects, catalytic sites, and enhanced electronic conductivity. Further, the core shell structure of Co3 O4 nanowires demonstrated a bifunctional activity for water splitting in 1 M KOH aqueous solution. From the hydrogen evolution reaction (HER), a current density of 10 mA cm −2 is achieved at a potential of −0.303 V vs. reversible hydrogen electrode (RHE). Meanwhile for the case of the oxygen evolution reaction (OER), a current density of 40 mA cm −2 is measured at a potential of 1.49 V vs. RHE. Also, this electrocatalyst has shown a considerable long-term stability of 15 h for both the HER and the OER. Importantly, electrochemical impedance spectroscopy has shown that the NiFeLDH integration onto cobalt oxide exhibited around 3 fold decrease of charge transfer resistance for both the HER and the OER in comparison with pristine cobalt oxide films, which reveals an excellent electrocatalytic activity for both faradaic processes. All these results confirm that the proposed electrocatalyst can be integrated into an efficient water splitting system.